A channeled spectro-polarimeter for ground based atmospheric monitoring - Albråten (My University, 2025)
Characterization of particle content in the atmosphere can be of both public health- and scientific interest. One way of characterizing the particle content, without the need of having the Sun behind the target, is by analyzing the polarization of the light incident from the direction of interest. This project has entailed the assembly and testing of a polarimeter capable of detecting the presence of varying particle content in the atmosphere, with high wavelength resolution. A detailed account of this process is described in this document, including some theoretical background to facilitate interpretation of the results. The principle of operation is similar to some existing instruments but adapted for practical inclusion into the volcanic monitoring network NOVAC, or other ground based enterprises such as monitoring of pollution in urbanized areas. Some work remains to scope the capacity of the instrument, but the basic capability has been verified.
Keywords: A channeled spectro-polarimeter for ground based atmospheric monitoring